Perception of firefighters on risk of exposure to respiratory health hazard : a qualitative analysis in Malaysia - Halim I; Mohd Fathulzhafran Mohamed Hanan; Ahmad Faiz T; Muhammad Alimin MR; Hanizah MY; Anaanthan BP; Muhammad Adil ZA (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Firefighters are exposed to multiple occupational hazards, where one of the hazards is chemical hazard that can affect the respiratory system. However, little is known regarding the perception of firefighters on the source of exposure to respiratory hazards, particularly in Malaysia. This work aims to explore the firefighter’s perspective on respiratory hazard exposure and to examine the compliance of the use of personal protective equipment (PPE). In-depth interviews were employed among 12 firefighters at Fire and Rescue Department of Malaysia in September 2020. The interview recordings were transcribed verbatim and of thematic analysis done via the NVIVO 12 programme. All participants were Malay, male, and married. The respiratory hazard exposure perceived can be divided into occupational source (e.g. exposure to smoke from firefighting, fire training, firefight demonstration, commuting, firefight vehicles: chemicals and dust) and non-occupational source (e.g. smoking). Firefighter recognised both the importance of wearing PPE and the fact they are still not compliant in wearing it. They also perceived wearing PPE as burden and having only a limited stock of PPE. Education and training need to be reinforced to strengthen firefighters’ risk perception, hazard identification, and risk assessment of hazards exposure. Strict standard operating procedure (SOP) and supervision during firefighters’ task is crucial to reduce hazard exposure and increase PPE compliance. Systematic and thorough inventory management is needed to ensure adequate PPE supply. Post qualitative analysis, the firefighters’ perception on respiratory hazard exposure was obtained, demonstrating that the analysis is ready for further study.